Oil palm empty fruit bunch (OPEFB) in thermosetting polymer composite / Ahmad Afham Ruzaidi, Normila Ahmad and Atef Anuar - Ruzaidi, Ahmad Afham; Ahmad, Normila; Anuar, Atef (2023)
The study of characteristics in natural fibres has intensified in recent decades. However, the application of its use is still not widespread due to the issue of environmental conditions. It affected increasing carbon dioxide (CO₂) emissions, significantly changing climate and weather. This research paper offers an idea that can be commercialised as a more decisive step in introducing natural fibre reinforcement polymer composite (NFRPC) products, especially on the performance of oil palm empty fruit bunch (OPEFB) into the Construction Industry market. The selection of methods in forming innovative products for this structural material is also essential to guarantee the condition of the more robust product. It is able to compete with the current market that is leading the industry. This is the reason for the future shift in the use of products or construction methods to ensure the sustainability of construction while simultaneously offering environmental conservation. This paper is prepared through a qualitative study, which wants explicitly to collect data with the proof of the study through laboratory experiments. This leads to the acquisition of performance data according to the purpose and objective of the study in fulfilling the desire to commercialise this innovation idea. The results of the study also lead to unique innovations contained in the study, allowing potential users to have confidence in evaluating and thus moving forward to the development of this product.